The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.08.30.274456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying seaweeds species of Chlorophyta, Phaeophyta and Rhodophyta using DNA barcodes

Abstract: Strengthening the DNA barcode database is important for a species level identification, which was lacking for seaweeds. We made an effort to collect and barcode seaweeds occurring along Southeast coast of India. We barcoded 31 seaweeds species belonging to 21 genera, 14 family, 12 order of 3 phyla (viz., Chlorophyta, Ochrophyta and Rhodophyta). We found 10 species in 3 phyla and 2 genera (Anthophycus and Chnoospora) of Ochrophyta were barcoded for the first time. Uncorrected p-distance calculated using K2P, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…Previous nationalised efforts to barcoding the marine diversity (Lakra et al, 2010;Bineesh et al, 2014;Bamaniya et al, 2015) along with localised efforts to barcode the diversity of Vellar estuary (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Sahu et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020;Narra et al, 2020) resulted in strengthening the reference library which insured that no ambiguous sequences were present in this study (as all sequences were identified to species level). Identification success was likely due to the use of previously generated references sequences from Indian waters from morphologically verified species and published through reference databases (such as GenBank and BOLD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous nationalised efforts to barcoding the marine diversity (Lakra et al, 2010;Bineesh et al, 2014;Bamaniya et al, 2015) along with localised efforts to barcode the diversity of Vellar estuary (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Sahu et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020;Narra et al, 2020) resulted in strengthening the reference library which insured that no ambiguous sequences were present in this study (as all sequences were identified to species level). Identification success was likely due to the use of previously generated references sequences from Indian waters from morphologically verified species and published through reference databases (such as GenBank and BOLD).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to capture potential genetic variation, including undocumented cryptic diversity, it is important to sequence an adequate number of individuals from across a species range (Weigt et al 2012b). We have made considerable efforts in the past decade as part of the Indian Census of Marine Life (ICoML) to recover barcodes in reasonable numbers of marine phyla including fin & shell fishes, invertebrates (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020) and plants (Sahu et al, 2016;Narra et al, 2020) occurring in and around the Vellar estuary. Hence we predict a high rate of success in identification of dietary items of A. maculatus occurring in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…1.6. Barcoding an Entire Regional Marine Flora Previous efforts of DNA barcoding of marine flora have focused either on (1) restricted geographic areas covering the three main macroalgal groups (Chlorophyta, Phaeophyceae, and Rhodophtya; e.g., northern Madagascar [80], Bergen, Norway [81], Boulder Patch, Beaufort Sea [82], southeast coast of India [83], Malta [84]), (2) larger areas (e.g., regional scale) but targeting specific groups (e.g., Rhodophyta in South Africa [85,86] and Qingdao, China [87]; Dumontiaceae [88] and Phyllophoraceae [89] in Canada; Rhodymeniales in Australia [90]; Gracilariaceae [91] and Pyropia [92] in the Republic of Korea), or (3) on lower taxonomic levels (e.g., genus, order, or family) but covering large geographic scales (e.g., Corallinophycidae in Altantic European maerl beds [93]). To our knowledge, no DNA barcoding study has yet been conducted at a regional level encompassing the three macroalgal groups (Chlorophyta, Ochrophyta, Rhodophyta), Cyanobacteria, and the marine phanerogams (seagrasses; marine phanerogams).…”
Section: Dna Barcoding Approachmentioning
confidence: 99%
“…Seaweeds are marine macroalgae that inhabit the littoral zone [ 11 ]. Seaweeds are characterized as non-vascular plants, which represent the primary producers in oceans and belong to the Protista not Planta kingdom [ 3 ].…”
Section: Introductionmentioning
confidence: 99%